Экономическая целесообразность применения энергосберегающих мероприятий с учетом степени эксплуатационной надежности - Анипко, О. Б.; Арсеньева, Ольга Петровна; Гогенко, А. А. (НТУ "ХПИ", 2004)
The economic aspect of municipal economy retrofit is observed purposing the increasing of energy saving. The retrofit of utilities supposes the replacement of old equipment. The substation of plate heat exchangers for Heating and Tap Water Supply is discussed in this paper. The probability of operational safety of heat ex-changer is determined. The proposes for plate heat exchangers’ maintaining schedule taking into account the existence of reserve heat exchanger are given.
Keywords: энергосбережение; пластинчатые теплообменные аппараты; эксплуатационные затраты; надежность